OP81 Long-term objective physical activity data from two primary care pedometer-based randomised controlled trials in middle-aged and older adults– are there still positive trial effects at 3 and 4 years?. (2nd September 2017) - Limb, E; Harris, T; Kerry, S; Victor, C; Iliffe, S; Ussher, M; Whincup, P; Furness, C; Wahlich, C; Cook, D; Ekelund, U; Fox-Rushby, J; et al.
Abstract : Background: The PACE-UP 3-armed primary care trial recruited 45–75 year olds into a 12 week pedometer-based intervention, with one postal intervention arm and one nurse support. The PACE-Lift 2-armed primary care trial recruited 60–75 year olds into a 12 week nurse-supported pedometer-based intervention. Both trials increased step-counts by around a tenth and time in moderate-to-vigorous physical activity (MVPA) in bouts by around a third at 12 months, with no difference between nurse and postal arms in PACE-UP. Long-term physical activity (PA) maintenance, particularly MVPA in bouts, is important for a wide range of health benefits, but few trials provide objective PA measures beyond 12 months. We followed up PACE-UP and PACE-Lift cohorts at 3 and 4 years respectively, to investigate whether intervention effects persisted. Methods: 3 year (PACE-UP) and 4 year (PACE-Lift) accelerometer outcomes were regressed on baseline accelerometry to estimate change in average daily step-counts and average weekly time in MVPA in ≥10 min bouts in the treatment groups compared to control groups. Imputation analyses were conducted to account for missing data effects. Results: PACE-UP 3 year follow-up rate was 67% (681/1023). Both intervention groups were still doing more steps/day than the control group: postal 627 (95% CI 198, 1056); nurse 670 (95% CI 237, 1102); nurse plus postal 648 (95% CI 272, 1024). The pattern was similar for total weekly MVPA in bouts: postal 28 (95% CI 7, 49); nurse 24 (95% CI 24 (3, 45); nurse plus postal 26 (95% CI 8, 44). PACE-Lift 4 year follow-up rate was 76% (225/298). In PACE-Lift the intervention versus control comparisons were 407 (95% CI −177, 992) for steps and 32 (95% CI 5, 60) for MVPA in bouts; though the steps comparison is not statistically significant, both the steps and MVPA estimates are consistent with the PACE-UP findings. Both trials showed no wear-time differences between groups and imputation analyses did not change results interpretation. Conclusion: Over two thirds of both trial cohorts provided long-term data. Both trials showed persistent effects on time in MVPA in bouts at 3 or 4 years. PACE-UP showed a significant persistent effect on step-counts and no difference between nurse and postal group outcomes. In PACE-Lift the step-count effect, while not statistically significant was consistent with both the PACE-UP findings and with the persistent significant effect for MVPA in bouts in PACE-Lift. These findings suggest that primary care pedometer interventions, delivered by post or with minimal contact, can make an important long-term contribution to addressing the public health physical inactivity challenge.